Ethics applied to medical students: Challenges for a new generation of health professionals - Silva, Pedro Henrique Janoario da; Perri, Laura Maria de Moura; Senne, Frederico Venâncio de; Abdalla, Douglas Reis (Seven Editora, 2023)
The Code of Ethics of the Medical Student is a fundamental tool to guide the ethical conduct of future physicians from the beginning of their training. This article discusses the importance of this code in the development of medical professionals committed to sound ethical principles and respect for the values of the profession. The code of ethics provides comprehensive guidelines for medical students, addressing areas such as integrity, respect for the patient, confidentiality, social and scientific responsibility, and relationship with other health professionals. In addition to establishing behavioral standards, the code also emphasizes the importance of self-reflection and continuous ethical improvement. Adherence to the code of ethics contributes to the training of compassionate and ethical physicians, who not only possess advanced medical knowledge, but also understand the moral responsibility inherent in the profession. By internalizing these values from their formative years, medical students are more likely to act with empathy, honesty, and respect when caring for their patients. In addition, the medical student's code of ethics promotes a culture of ethics and responsibility, positively impacting the environment of medical teaching and practice. Applying these principles not only benefits patients, but also strengthens trust in the medical profession as a whole. In conclusion, the Code of Ethics of the Medical Student plays a crucial role in the training of future ethical and competent physicians. By incorporating ethical principles from the beginning of their academic journey, medical students are better prepared to meet the complex challenges of medical practice, while always maintaining the highest standards of ethics and integrity. DOI:https://doi.org/10.56238/innovhealthknow-010